How does portfolio use support self-regulated learning during general practitioner specialty training? A qualitative focus group study - Anneke Kramer; Margaretha H Sagasser; Bart Thoonen; Angelique A Timmerman; Rozemarijn van der Gulden; Nynke Scherpbier-de Haan; Sylvia Heeneman (BMJ Open)
Objectives Portfolios are used to support self-regulated learning (SRL), but the research literature is still inconclusive on their effectiveness. This study explored experiences with portfolio use among different stakeholders, to answer the research question: How does portfolio use support SRL during general practitioner (GP) specialty training?Design We used a qualitative research design, based on phenomenology.Setting Three of the eight training institutes of Dutch GP specialty training participated in this study.Participants The three stakeholder groups that use the portfolio were included in nine homogenous focus groups: trainees (n=16), supervisors (n=16) and faculty (n=17). All participants had at least 6-month experience with portfolio use.Results Three themes were identified: SRL with(out) the portfolio, stakeholder dynamics and ambiguities. Respondents were doubtful about the learning benefits of portfolio use, as most trainees used their portfolio to ‘check off’ what was considered required. Stakeholder dynamics contributed to checking off behaviour in two ways. First, trainees experienced documenting learning activities to be superfluous, since the close relationship with their supervisor already supported SRL sufficiently. Second, faculty often (unintentionally) took portfolio ownership away from trainees, as they instructed trainees to deliver portfolio content that was valuable for assessment. Without ownership, trainees struggled to use the portfolio for SRL. Besides, ambiguities related to portfolio use amplified checking off behaviour.Conclusions Portfolio use did not support SRL in our setting. The multipurpose use of the portfolio (for the support of SRL and assessment) was identified as the primary obstacle. Underlying is a conflict that is often present in current medical curricula: agency versus accountability. If the support of SRL is considered a valuable and attainable purpose of portfolio use, it is important to realise that deliberate attention for this purpose is required during the design, guidance, assessment and evaluation of the portfolio.